The Legal Responsibility of Influencers in Digital Media Content and its Impact on the Behavior of High School Students in Riyadh (The International Journal of Educational Sciences and Arts, 2025)
This study aims to explore the impact of the legal liability of digital media influencers on the behavior of high school students in Riyadh, in light of the increasing influence of social media in shaping attitudes and behaviors. The study used a descriptive survey approach, selecting a random sample of 80 male and female students from various areas of Riyadh. A questionnaire was used to collect data from the students. The results showed that influencers have a clear impact on student behavior in terms of thinking, interaction, and imitation. There were also statistically significant differences in the degree of influence by gender, in favor of females, and by academic level. The study recommended strengthening family and school oversight, spreading legal and media awareness among students, and regulating content published on digital platforms in a manner consistent with educational and social values.
Keywords: Influencers; Digital Media; Legal Responsibility; High School Students; Student Behavior; Digital Content; Media Laws